Turkey - Education Sector Study : Sustainable Pathways to an Effective, Equitable and Efficient Education System for Preschool through Secondary School Education, Executive Summary - World Bank (Washington, DC, 2012)
This Education Sector Study (ESS) is the World Bank's response to the need for a comprehensive study of Turkey's education system, in light of the dramatic changes that are sure to alter the country's social and economic landscape over the next decade. The study was prepared in association with the Education Reform Initiative of the Istanbul Policy Center on the basis of research and dialogue with a wide array of education stakeholders and actors. The overall objective of the ESS is to provide an assessment of current challenges to the education system in Turkey and identify policy options that can complement the country's existing pre-tertiary education strategy. Volume one provides a complete description of challenges, conclusions, and policy options for the reform of pre-school, primary, and secondary education. It includes an Annex that summarizes the research studies and policy notes commissioned to inform the report. Volume II is a collection of the complete research studies and policy notes commissioned for the ESS report.